2020
DOI: 10.2320/matertrans.l-m2020856
|View full text |Cite
|
Sign up to set email alerts
|

Color Metallography of Characteristic Microstructure in High-Speed Twin-Roll Cast Al–Mn–Si Alloy Strip Using Weck’s Reagent

Abstract: A color metallography using Weck's reagent was employed to investigate the characteristic microstructure of AlMnSi alloy strip fabricated by high-speed twin-roll casting. The microstructure of the strip consists of two components: solidified shells and a central band. By Weck's reagent etching, the colorful microstructure was obtained, and doughnut-like patterns were observed in the globular grains. Based on the presence of the patterns, the globular grains were divided into two types: Type-I and Type-II. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This reagent causes regions rich in the alloying element to become bright, and regions rich in Al to become dark. 7) A band zone existed in the center of the thickness direction; this is characteristic of high-speed roll casting. 7) There was a tendency for the band zone to form under high-speed roll casting at smaller roll loads than for the CHTRCA.…”
Section: Band Zone In Cast Strip At Roll Bitementioning
confidence: 99%
See 3 more Smart Citations
“…This reagent causes regions rich in the alloying element to become bright, and regions rich in Al to become dark. 7) A band zone existed in the center of the thickness direction; this is characteristic of high-speed roll casting. 7) There was a tendency for the band zone to form under high-speed roll casting at smaller roll loads than for the CHTRCA.…”
Section: Band Zone In Cast Strip At Roll Bitementioning
confidence: 99%
“…7) A band zone existed in the center of the thickness direction; this is characteristic of high-speed roll casting. 7) There was a tendency for the band zone to form under high-speed roll casting at smaller roll loads than for the CHTRCA. The band zone formed up to the roll bite.…”
Section: Band Zone In Cast Strip At Roll Bitementioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence mechanism of surface cracks in the strip cast using the VHSTRC was precisely investigated by Kumai and Hrada. 4,5) It was reported that solution-rich liquid, which existed between the dendrites and at the grain boundary in the center area in the thickness direction, was squeezed by solidification shrinkage to the strip surface. The brittle ¢-Al 3 Mg 2 solidified, and cracking occurred at ¢-Al 3 Mg 2 .…”
Section: Introductionmentioning
confidence: 99%